Pengaruh Mekanisme GCG Terhadap Konservatisme Akuntansi Pada Perusahaan BUMN - Saputri, Maya Aulia; Lindrianasari, Lindrianasari; Asmaranti, Yuztitya; Dharma, Fitra (Department of Accounting, Faculty of Economics and Business, Universitas Tadulako, 2021)
The purpose of this study is to examine the effect of mechanism of good corporate governance to accounting conservatism. Mechanism of good corporate governance are represented by three variables, namely composition of the board of independent commissioners, institutional ownership, and audit committee. The population are all state-owned enterprises listed on Indonesian Stock Exchange on 2015-2016, amounting to 20 companies. The data analysis technique used multiple regression analysis. Hypothesis testing is done using multiple linear regresion. The results show that the composition of the board of independent commissioners and institutional ownership has no influence on accounting conservatism, and variable audit committee has a positive influence on accounting conservatism.